The construction of shame in the Hebrew Bible : the prophetic contribution - Stiebert, Johanna (Journal for the study of the Old Testament. Supplement series, 2002)
This book explores the phenomenon of shame in the Hebrew bible. It focuses particularly on the major prophets, because shame vocabulary is most prominent there. Shame has been widely discussed in the literature of psychology and anthropology; the book discusses the findings of both disciplines in some detail. It emphasises the social-anthropological honour/shame model, which a considerable number of biblical scholars since the early 1990s have embraced enthusiastically. The author highlights the shortcomings of this heuristic model and proposes a number of alternative critical approaches.